Antidumping as strategic trade policy under asymmetric information - Xenia Matschke; Anja Schöttner (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper investigates the domestic government's antidumping duty choice in an asymmetric information framework where the foreign firm's cost is observed by the domestic firm, but not by the government. To induce truthful revelation, the government can design a tariff schedule, contingent on firms' cost reports, accompanied by a threat of auditing and implementing penalty duties. We show that the antidumping framework within GATT/WTO may not only offer the means to pursue strategic trade policy disguised as fair trade policy, but may also help overcome the informational problems with regard to determining the optimal strategic trade policy.
Keywords: F12; F13; 330; Antidumping duties; asymmetric information; trade protection; strategic trade policy; Antidumping; Strategische Handelspolitik; Asymmetrische Information; Spieltheorie; WTO-Regeln; Theorie; Welt